753 Combination of cellular assays with metabolomics revealed mechanistic insights on dose-response relationship of 3-nitrobenzanthrone in human urothelial cancer cells. (24th April 2018) - Schmitz-Spanke, Simone; Verma, Nisha; Zerries, Anna; Pink, Mario
Abstract : Introduction: A product of incomplete combustion of diesel fuel, 3-nitrobenzanthrone (3-NBA), has been classified as a cancer-causing substance. It gained attention as a potential urinary bladder carcinogen due to the presence of its metabolite in urine and formation of DNA adducts. The aim of this study was to characterise the dose-response relationship starting from environmentally relevant to high concentrations by utilising toxicological and metabolomic approaches to determine the toxic potential of 3-NBA in bladder cells. Method: Cells of RT4 cells were exposed against 0.3 nM to 80 µM 3-NBA for 24 hour. Both activity of enzymes involved in the metabolism of 3-NBA as well as cytotoxicity were determined using specific assays. Finally, the potential of 3-NBA to alter the cellular metabolism was assessed by gas chromatography-mass spectrometry. Result: RT4 cells were capable of bioactivation of 3-NBA within 30 min, whereas the main contributor for bioactivation of 3-NBA was NAD(P)H:quinone oxidoreductase (NQO1). Cytotoxicity assessment revealed an activation of adaptive mechanisms at low dosages, which diminished at higher doses. The metabolomic analysis of the cells showed elevated levels of various antioxidants at low concentrations of 3-NBA. At higher exposure concentrations, it appeared that the cells reprogrammed their metabolism to maintain the pentose phosphate pathway (PPP) aiding in cell protection. Discussion: Starting from a relevant environmental dose of 0.0003 µM up to 80 µM, we described the driving mechanism behind the different cellular states – in particular an activation of adaptive mechanisms at low dosages, which diminished at higher doses. The metabolomic data suggested that the PPP and the folate metabolism play a leading role in this transition. Moreover, there was evidence for an additional carbon flux into PPP via the gluconate metabolism to support the formation of NADPH, which in term is an important determinant of the defence system against oxidative stress.